Preoperative prediction of parathyroid carcinoma in an Asian Indian cohort. Issue 7 (10th March 2021) - Shah, Ravikumar; Gosavi, Vikrant; Mahajan, Abhishek; Sonawane, Sushil; Hira, Priya; Kurki, Vineeth; Bal, Munita; Sathe, Pragati; Pai, Prathamesh; D'Cruz, Anil; Uchino, Shinya; Garale, Mahadeo Namdeo; et al.
Abstract: Background: Parathyroid carcinoma (PC) requires preoperative prediction for appropriate surgical management. Differentiation from symptomatic primary hyperparathyroidism (sPHPT) cohort is difficult. Methods: Patients with sPHPT from a tertiary‐care center, Western India, including Cohort‐A ( n = 19 [10/M; 9/F]) with PC and Cohort‐B ( n = 93 [33/M; 60/F] with benign parathyroid lesions) were compared to derive predictors for differential diagnosis. Results: There were no differences in clinical or biochemical parameters between the two cohorts. Comparison of CECT parameters showed that irregular shape, tumor heterogeneity, infiltration, short/long‐axis ratio >0.76, and long‐diameter >30 mm had high negative‐predictive value and intratumoral calcification had 100% positive‐predictive value to diagnose PC; whereas there were no differences in contrast‐enhancement patterns. Long diameter, short/long‐axis ratio, and heterogeneity were significant predictors on multivariate analysis. Conclusion: It is difficult to predict diagnosis of PC in an Indian sPHPT cohort based on clinical and biochemical parameters, whereas CECT parathyroid‐based parameters can aid in diagnosis.